Psychological skills training impacts autonomic nervous system responses to stress during sport-specific imagery: An exploratory study in junior elite shooters - Lee, Gunyoung; Ryu, Jihoon; Kim, Teri (Frontiers in Psychology, 2023)
This study investigated the effects of psychological skills training (PST) in shooters psychophysiologically using heart rate variability (HRV) in addition to psychological questionnaires and participant interviews. Five junior pistol shooters participated in an eight-week PST program consisting of a group session per week followed by individual counseling. Before and after PST, we collected electrocardiography data during rest, mental imagery of sport-related crisis situations, and successful performance, to analyze differences in HRV indices. Participants also responded to the Psychological Skills Inventory for Archery and Shooting (PSIAS), Intrinsic Motivation Inventory (IMI), Sports Anxiety Scale (SAS), and Trait Sport Confidence Inventory (TSCI). Results showed that the perceived competence (pre: 2.52±0.95, post: 3.36±0.73, p = .049) and trait sport confidence (pre: 4.94±1.17, post: 6.60±0.65, p = .049) significantly improved after PST. The analysis of HRV indicated that the ratio of low-frequency power to high-frequency power (LF/HF ratio) decreased significantly during imagery of crisis (pre: 3.4±2.3, post: 1.014±0.71, p = .038) and success (pre: 1.933±0.917, post: 0.988±0.572, p = .046), reflecting a strengthened autonomic nervous system’s responsiveness to stress. Our findings illustrate that PST can help athletes better cope with psychologically disturbed situations during competition, by providing psychophysiological evidence through HRV changes.